Political Cycles : The Opposition Advantage - Pascal Gautier; Raphael Soubeyran (Fondazione Eni Enrico Mattei (FEEM), 2005)
We propose a two dimensional infinite horizon model of public consumption in which investments are decided by a winner-take-all election. Investments in the two public goods create a linkage across periods and parties have different specialities. We show that the incumbent party vote share decreases the longer it stays in power. Parties chances of winning do not converge and, when the median voter is moderate enough, no party can maintain itself in power for ever. Finally, the more parties are specialized and the more public policies have long-term effects, the more political cycles are likely to occur.
Keywords: D72; H41; C72; 330; Cycles; Alternation; Public goods; Advantage; Opposition; Politischer Konjunkturzyklus; Öffentliches Gut; Median Voter; Öffentlicher Konsum; Theorie